[Math] Prove $A + (B+C) =B+(A+C) = C+ (A+B)$ using the definition of $A+B$

elementary-set-theorylogic

Let $A$ and $B$ be sets. Define the symmetric difference of $A$ and $B$, written $A+B$, by $A+B=(A \cup B) \backslash (A \cap B)$.

Prove the following statement

$A + (B+C) = B+(A+C) = C+ (A+B)$

This is a mixture of associative law and commutative law.

Proof using associative law which states that for all statements $P,Q$ and $R$.

$(P \land Q) \land R \leftrightarrow P \land (Q \land R)$ and $(P \lor Q) \lor R \leftrightarrow P \lor (Q \lor R)$

$A + (B+C) $

$A + (B \cup C) \backslash (B \cap C)$

$$
\begin{array}{c}
A+(B+C)\\
A+[(B \cup C) \setminus (B \cap C)]\\
(A \cup [(B \cup C) \setminus (B \cap C)]) \setminus (A \cap [(B \cup C) \setminus (B \cap C)])\\
\end{array}
$$

$B + (A + C )$

$B + (A \cup C) \backslash (A \cap C)$

$$
\begin{array}{c}
B+(A+C)\\
B+[(A \cup C) \setminus (A \cap C)]\\
(B \cup [(A \cup C) \setminus (A \cap C)]) \setminus (B \cap [(A \cup C) \setminus (A \cap C)])\\
\end{array}
$$

$C + (A+B) $

$C + (A \cup B) \backslash (A \cap B)$

$$
\begin{array}{c}
C+(A+B)\\
C+[(A \cup B) \setminus (A \cap B)]\\
(C \cup [(A \cup B) \setminus (A \cap B)]) \setminus (C \cap [(A \cup B) \setminus (A \cap B)])\\
\end{array}
$$

Proof for commutative law which claims that for all statements $P$ and $Q$

$P \land Q \leftrightarrow Q \land P$ and $P \lor Q \leftrightarrow Q \lor P$

$$
\begin{array}{c}
A+(B+C) = (B+C)+A \\
A + (B \cup C) \backslash (B \cap C) = (B \cup C) \backslash (B \cap C) + A\\
\end{array}
$$

$$
\begin{array}{c}
B+(A+C) = (A+C)+B \\
B + (A \cup C) \backslash (A \cap C) = (A \cup C) \backslash (A \cap C) + B\\
\end{array}
$$

$$
\begin{array}{c}
C+(A+B) = (A+B)+C \\
C + (A \cup B) \backslash (A \cap B) = (A \cup B) \backslash (A \cap B) + C\\
\end{array}
$$

I don't know what to do next…I'm not even sure if this is correct either.

Best Answer

Perhaps the simplest proof is via Venn diagrams.

enter image description here

The usual method of showing $A+(B+C) = B + (A+C)$ is to prove

  1. $A+(B+C) \subseteq B + (A+C)$ and
  2. $B + (A+C) \subseteq A+(B+C)$